2018
DOI: 10.5897/jdae2017.0890
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and profitability of potato production by smallholder farmers: The case of Dinsho District, Bale Zone of Ethiopia

Abstract: . Cross sectional data collected in 2015/16 production year from 147 surveyed households was utilized in achieving these objectives. Non-parametric net crop revenue analysis and Cobb-Douglas stochastic frontier approach were used to analyze enterprise profitability and to estimate the technical efficiency levels in potato production, respectively. The result of net crop revenue analysis indicated that potato production was profitable wherein the producers had earned net return of about 11,740.9 ETB (Ethiopian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 3 publications
(4 reference statements)
4
20
0
1
Order By: Relevance
“…This implies that majority of the respondents are in their active age. This finding is similar to that of Adio and Oladele, (2021) who reported in a study on food security and its determinant on farming household in Surulere Local Government of Oyo State that the mean age of the respondents was 50.91 yearsand Ahmed et al, (2018), in which he observed that youth constitute the majority of the maize farmers. The result of the gender structure of the respondents in Table 1 revealed that the maize farmers were dominated by males, accounting for 80 percent while female accounted for 20 percent.…”
Section: Socio-economic Characteristicssupporting
confidence: 90%
“…This implies that majority of the respondents are in their active age. This finding is similar to that of Adio and Oladele, (2021) who reported in a study on food security and its determinant on farming household in Surulere Local Government of Oyo State that the mean age of the respondents was 50.91 yearsand Ahmed et al, (2018), in which he observed that youth constitute the majority of the maize farmers. The result of the gender structure of the respondents in Table 1 revealed that the maize farmers were dominated by males, accounting for 80 percent while female accounted for 20 percent.…”
Section: Socio-economic Characteristicssupporting
confidence: 90%
“…The financial feasibility was assessed from the Revenue Cost Ratio (RCR), Benefit Cost Ratio (BCR), and Marginal Benefit Cost Ratio (MBCR). The financial feasibility analysis was done by adopting several previous studies, including [11], [12], [13] and [14] with the following formula: Marginal Benefit Cost Ratio (MBCR) is useful to determine whether a new technology used by farmers can bring added value. MBCR value > 1 means that the introduced technology has the potential to be developed because it is economically feasibility.…”
Section: Methods Of Study Implementationmentioning
confidence: 99%
“…In addition to this, elderly people in TIS who reach the age of 60 and above gain access to income in the form of social grants, hence they enjoy minimum incentives to engage in irrigation farming. Ageing has a diminishing effect on the performance of irrigation schemes and food security (Dube, 2018). Ageing affects the technical efficiency of the agricultural systems as older farmers are unwilling to change their practices and slow to adopt new technologies (Senyolo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%